Radon emanation from phosphogypsum and related mineral samples in Cyprus - Lysandrou, Michaela; Charalambides, Antonios; Pashalidis, Ioannis (My University, 2007)
Radon emanation rates from phosphogypsum samples have been determined to assess the radiological impact of radon emanated from a phosphogypsum disposal site. For comparison corresponding measurements were conducted with samples of phosphate rock, fertilizer, natural gypsum, and calcite. The experimental data show that phosphate rock and phosphogypsum samples emanate radon in significantly higher rates (up to almost two orders of magnitude). The exhalation rates determined for samples obtained from a phosphogypsum stack in Cyprus range from 0.35 to View the MathML source. This, consequently, may result in increased radon levels in dwellings build and excessive radiation exposure to workers residing on the stack, which could reach in extreme cases values up to View the MathML source.
Keywords: Radon; Phosphogypsum; Minerals; Exhalation rates; Radiological impact